The precipitates and properties evolution behaviors of AlZnMgCu alloy during the retrogression process with slow heating - Nianmei Han; Di Feng; Xinmin Zhang; Shengdan Liu (Journal of Materials Research and Technology, 2023)
In order to develop the retrogression and re-aging (RRA) effect on the performance of AlZnMgCu alloy products with large scale, the hardness, electrical conductivity, tensile properties, and exfoliation corrosion resistance of the Al7.7Zn2.1Mg2.0Cu alloy were investigated at two pre-aging temperatures and a 3 °C/min retrogression heating rate. Transmission electron microscopy (TEM) was used to investigate the evolutions of precipitates at different RRA routes. Results revealed that the standard compliant performances could also achieved by setting the pre-aging as the under-aged state when the slow retrogression heating rate existed. Continuous precipitation occurred at the early stage of heating retrogression. The dissolution behavior of the GP zone with the radius lower than the critical value had finished in heating retrogression. The η′ phase re-precipitated firstly in the isothermal retrogression, then grew and coarsened with the retrogression time increase. During the whole retrogression including heating and isothermal stages, the hardness undergone an “up-down-up-down” transversion. After RRA-treated at (105 °C, 24 h + (heating to 190 °C at 3 °C/min)190 °C, 50 min +120 °C, 24 h), excellent corrosion resistance achieved with only a 5.5% sacrifice of tensile strength when compared to peak aged state. Due to the slow temperature-rising process in retrogression for the large section products, the optimized RRA schedule is more practical for industrial applications.